Problematics of Elementary Teachers’ Readiness in Facing Parents’ Attitudes - Hidayani, Nurul; Fantini, Lisa (International Journal of Students Education, 2023)
Create activity Study effective teaching in schools need role of teacher, child And also parents. Good communication can ensure ongoing connection between teachers , students and parents in a way perfect . School need build communication with parents , because of the process of parental interaction with child Far more strong And open anywhere with involving parents to in education school For build character child become good choice. One effective way to prevent violence in the school environment is to establish good communication between students, parents and teachers. Type of data used writer in study This is the data obtained from literature study . Literature study is the method used For following data or related sources degan topic raised in something study from library and internet. Related theories and related ideas with study. This journal will discuss the importance of communication between teachers and parents. The type of data used by the author in this research is data obtained from literature studies. In the process of writing this journal, the author collected all data related to the discussion theme, namely regarding teacher readiness in dealing with parental attitudes. This article aims to create better collaboration between schools and families, which will support maximum child development.